Sticking to the facts : 10 ways to fight misinformation - Craigie, Gregor (Orca take action!, 2026)
"Part of the nonfiction Orca Take Action series for middle-grade readers, this illustrated book gives young readers tools to spot fake news and actions to take to fight misinformation and disinformation."--